Merrifield resin modified with thiacalixarene-tetraphosphonates: synthesis, characterization and europium sorption - Lukashova, M.S.; Belikov, K.N.; Bryleva, K.Yu.; Kharchenko, S.G.; Vishnevsky, S.G.; Kalchenko, V.I. (Functional Materials, 2016)
Tetrahydroxythiacalixarene tetraphosponates were synthesized and chemically linked to chloromethylated polystyrene (Merrifield resin) surface via the Williamson reaction. In order to evaluate the effect of thiacalixarene platform structure on the properties of sorbents, phosphorylated resins with P=O groups attached to the polymer surface via methylene spacers were synthesized by the Arbuzov reaction of the iodomethylpolysterene with trialkylphosphites. Composition and structure of the obtained materials was established by elemental analysis and IR spectroscopy. The sorbents obtained remove up to 99 % of Eu(III) ions from aqueous solutions of average mineralization level at pH of 5.5-6. The optimum contact time was established to be 2 h. Due to cooperative (macrocyclic) effect of P=O binding groups pre-organized at the upper rim of the thiacalixarene platform the resins exhibit better uptake parameters than the resins modified with para-unsubstituded, para-tert-butylsubstituted thiacalixarenes or the resins bearing the phosphonate groups directly bound to the Merrifield resin surface. Europium distribution coefficient for the best sorbents obtained was equal to 11.3.